Business Actors’ Liability for Consumer Losses in the Case of Hazardous Syrup Medicines under Law Number 8 of 1999 concerning Consumer Protection: Tanggung Jawab Pihak Usaha atas Kerugian Konsumen dalam Kasus Obat Sirup Berbahaya berdasarkan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Purba, Nanda Divabuena; Sudiro, Amad (Indonesian Journal of Law and Economics Review, 2025)
General Background: The circulation of hazardous syrup medicines causing acute kidney failure in children has revealed fundamental weaknesses in Indonesia’s consumer protection and health monitoring systems. Specific Background: Although Law No. 8 of 1999 on Consumer Protection regulates the obligations of business actors, ineffective supervision by both producers and regulatory agencies such as BPOM has led to serious public health risks and consumer losses. Knowledge Gap: Existing studies have not sufficiently examined the legal accountability of business actors and the state’s preventive role in safeguarding consumer rights in the pharmaceutical sector. Aims: This study analyzes the scope of business actors’ liability and assesses the effectiveness of legal protection for consumers in the case of hazardous syrup medicines. Results: The research finds that business actors bear strict liability under Articles 8 and 19 of the Consumer Protection Act, covering civil, administrative, and criminal responsibility for consumer damages. Novelty: The study exposes a significant gap between legal norms and their practical implementation, underscoring the need for coherent enforcement and institutional coordination. Implications: Strengthening preventive and repressive legal frameworks, regulatory oversight, and corporate ethical responsibility is essential to ensure justice, consumer safety, and legal certainty within Indonesia’s consumer protection regime. Highlights: Business actors hold strict liability for unsafe pharmaceutical products. There is a gap between regulation and implementation in consumer protection. Stronger preventive and repressive legal mechanisms are urgently needed. Keywords: Business Liability, Consumer Protection, Hazardous Syrup, Legal Accountability, Public Health